Determining Hurwitz Components of A8 - Salih, Haval M. Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2016)
Let be a finite group, the Hurwitz space is the space of genus covers of the Riemann sphere with branch points and the monodromy group . In this paper, we give a complete list of primitive genus zero systems of . We determine the braid orbits on the suitable Nielsen classes, which is equivalent to finding connected components in . We achieve this with the aid of the computer algebra system GAP and the MAPCLASS package.
Keywords: Braid orbits; Hurwitz orbits